2022
DOI: 10.3389/fonc.2022.1005924
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic FDG-PET imaging for differentiating metastatic from non-metastatic lymph nodes of lung cancer

Abstract: Objectives18F-fluorodeoxyglucose (FDG) PET/CT has been widely used in tumor diagnosis, staging, and response evaluation. To determine an optimal therapeutic strategy for lung cancer patients, accurate staging is essential. Semi-quantitative standardized uptake value (SUV) is known to be affected by multiple factors and may fail to differentiate between benign and malignant lesions. Lymph nodes (LNs) in the mediastinal and pulmonary hilar regions with high FDG uptake due to granulomatous lesions such as tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In a later study, normal values for [ 18 F]FDG uptake in selected tissues were estimated and no difference was observed between malignant and non-malignant [ 18 F]FDG avid lesions in MR FDG images [ 34 ]. In contrast to this, a study examining 135 LN in 29 patients with lung cancer found that values could discriminate malignant from benign LN [ 40 ], while an additional, pathological verified, liver lesion was detected in a population of 18 oncological patients [ 37 ]. In the present study, the assessment of MR FDG images resulted in the identification of two extra potential locoregional LN metastasis, one in the axillary level I and one located parasternal.…”
Section: Discussionmentioning
confidence: 99%
“…In a later study, normal values for [ 18 F]FDG uptake in selected tissues were estimated and no difference was observed between malignant and non-malignant [ 18 F]FDG avid lesions in MR FDG images [ 34 ]. In contrast to this, a study examining 135 LN in 29 patients with lung cancer found that values could discriminate malignant from benign LN [ 40 ], while an additional, pathological verified, liver lesion was detected in a population of 18 oncological patients [ 37 ]. In the present study, the assessment of MR FDG images resulted in the identification of two extra potential locoregional LN metastasis, one in the axillary level I and one located parasternal.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnostic efficacy, the previous study performed by Skawran et al in 60 cancer lesions and 17 inflammatory/infectious lesions has shown that using a cut-off value for Kimax-60 min of 0.026 ml/g/min delivers a sensitivity of 63.3% and a specificity of 82% for the detection of cancer lesions [ 42 ]. And previous research by our team also found that a cut-off value of Ki-65 min of 0.022 ml/g/min was identified as the optimal compromise point between sensitivity and specificity, with values of 39.50% and 91.80%, respectively, in discriminating between metastatic ( n = 86) and non-metastatic LNs ( n = 49) of lung cancer, and concluded that Ki with high specificity provided a complementary value to SUVmax [ 8 ]. The study performed by Ye Q et al strongly indicated that Ki from dynamic PET can provide superior discrimination between benign and malignant lung nodules than SUV [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…While comparing the rate constant values of K1, k2, and k3 estimated by 18 F-FDG, Ki was more commonly used and had been shown to be useful for characterizing tumor metabolism and assessing therapy response by reflecting more accurate changes after therapy [ 11 15 ]. The Ki was superior to SUV in differential diagnosing solitary lung nodules and lymph nodes (LNs), as well as in delineating tumor volume [ 6 8 , 16 ]. However, the long acquisition time, single bed-position dynamic acquisition (axial extent of view of 15-25 cm), invasive arterial blood sampling, large volume of post-processed data, and the relatively complex process limit the routine use of dynamic PET in clinical practice [ 5 , 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of FDG PET images to discover the heterogeneous metabolic response to treatment in patients with NSCLC found patients with a high metabolic response are significantly associated with poor prognosis [ 39 ]. The additional kinetic parameters such as K1, k2, Ki, and Ki/K1 in the dynamic PET scan, compared with SUV max , were associated with not only the metabolic condition of the lesion but also its blood flow and microenvironment [ 40 ], in order to differentiate metastatic and non-metastatic LNs. It appears that the combination of imaging biomarkers and serum metabolites or protein levels could become a feasible tool in the prediction of the prognosis of patients with lung cancers.…”
Section: Discussionmentioning
confidence: 99%